Assessment of nutritional status of patients of congenital pouch colon following definitive surgery - Nand Kishor Shinde; Praveen Kumar; Pradeep Kumar Dabla; Praveen Jhanwar; Rajiv Chadha; Subhasis Roy Choudhury (Wolters Kluwer Medknow Publications, 2017)
Purpose: To assess the nutritional status in 31 patients of congenital pouch colon (CPC) who had undergone definitive surgery and closure of a protective stoma, if any, at least 1 year earlier and were below 14 years age. Materials and Methods: The clinical history, demographic details, anthropometric measurements, and results of hematological and biochemical tests were recorded. In addition to collective data, analysis was also performed after grouping by age, subtype of CPC (Types I/II and Types III/IV CPC), and in Types I/II CPC patients, by whether the colonic pouch had been completely excised or else a segment preserved by tubular colorraphy (TC). Results: Severe fecal incontinence (FI) was common (64.52%). Anthropometry showed a significant malnutrition in 53.85-95.45% patients, especially "stunting" which was most prevalent in the 0-5 years age-group. Serum Vitamin B 12 , folate, and Vitamin D were lower than normal in 38.71%, 22.58%, and 74.19% patients, respectively, without statistically significant difference among the various groups studied. Patients with Types I/II CPC had a statistically significant higher incidence of anemia, low serum ferritin, and severe FI than patients with Types III/IV CPC. Patients with Types I/II CPC, managed by excision of the colonic pouch, had a higher incidence of severe FI, wasting, and thinness than those undergoing TC. Conclusions: On follow-up of the patients of CPC, anthropometry shows a high incidence of malnutrition, especially stunting in the 0-5 years age-group. There is an adequate adaptation of fluid-electrolyte homeostasis. Although Types I/II CPC patients have a significantly higher incidence of anemia and severe FI than Types III/IV CPC patients, long-term anthropometric parameters are similar. In Types I/II CPC, preservation of the colonic pouch by TC offers long-term benefit.